Plasma cell cheilitis - Harim Tavares dos Santos; John Lennon Silva Cunha; Lucas Alves Mota Santana; Cleverson Luciano Trento; Antônio Carlos Marquetti; Ricardo Luiz Cavalcanti de Albuquerque-Júnior; Sílvia Ferreira de Sousa (University of São Paulo, 2019)
Plasma cell cheilitis (PCC) is an inflammatory disorder of unknown etiology that affects the lip. It is characterized histologically by a dense infiltrate of plasma cells with a variety of clinical features. The response to different therapeutic modalities is controversial, especially regarding the effectiveness of corticosteroids. We present a case of a 56-year-old Caucasian man with a painful ulcerated and crusted area in the lower lip, resembling a squamous cell carcinoma or actinic cheilitis. Topical corticosteroid was used for one week, which resulted in partial regression and motivated a biopsy. The histological examination provided the diagnosis of PCC. The patient has been disease-free for six months. We also provide a discussion on the criteria of differential diagnosis and management of this rare condition.